2015
DOI: 10.1016/s1701-2163(15)30311-x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical and Neonatal Outcomes of Methadone-Maintained Pregnant Women: A Canadian Multisite Cohort Study

Abstract: Integrated care programs resulted in satisfactory obstetrical and neonatal outcomes for pregnant women on MMT. Policies promoting maternal-newborn contact, rooming-in, and breastfeeding may help to decrease the severity of NAS and the need for pharmacological treatment of NAS. We strongly recommend the development of similar programs across Canada to address gaps in services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…SOGC's policy paper reports that breastfeeding initiation among women on opioid maintenance therapy is as low as 20% to 75% and decreases further by 6 to12 weeks postpartum . A retrospective chart review of 94 women on methadone maintenance therapy conducted in Vancouver, Montreal, and Toronto who received care between 1997 and 2009 found a 17% initiation rate that did not vary significantly by city . The low rate of breastfeeding among women on opioid maintenance therapy raises the question of why this is the case; the best way to answer such a question is to ask the women themselves.…”
Section: Resultsmentioning
confidence: 99%
“…SOGC's policy paper reports that breastfeeding initiation among women on opioid maintenance therapy is as low as 20% to 75% and decreases further by 6 to12 weeks postpartum . A retrospective chart review of 94 women on methadone maintenance therapy conducted in Vancouver, Montreal, and Toronto who received care between 1997 and 2009 found a 17% initiation rate that did not vary significantly by city . The low rate of breastfeeding among women on opioid maintenance therapy raises the question of why this is the case; the best way to answer such a question is to ask the women themselves.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Integrated mother-infant care leads to optimal outcomes for healthy mothers and infants, including those with neonatal abstinence syndrome. 33 Rooming-in also provides more security, may avoid newborn abductions or switches, leads to decreased infant abandonment, 34 and provides more opportunity for supervised maternalnewborn interactions. 35 Hospital staff members caring for mother-infant dyads have more opportunities to empower mothers to care for their infants than when infant care is conducted without the mother and in a separate nursery.…”
Section: Evidence For Ssc and Rooming-inmentioning
confidence: 99%
“…5 Maternal-newborn contact, rooming-in, and breastfeeding may help to decrease the severity of NAS and the need for pharmacological treatment of NAS. 5,6 In our study of one rural hospital over a 15 month period, we found that our incidence of symptomatic NAS infants was 33 per thousand. Most of these infants were not identified during a prenatal history or prenatal urine drug screen.…”
Section: Discussionmentioning
confidence: 77%